2003
DOI: 10.1021/ja036384l
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Surface Molecular Hydrates on Solid Sulfuric Acid Films

Abstract: Infrared spectroscopic and secondary ion mass spectrometric studies reveal the presence of a stable molecular hydrate on the surface of condensed thin films of ionic sulfuric acid hydrates. This surface species is observed to play a role in the interaction of ammonia, reacting rapidly until the material is depleted. A slower, continuous process is also observed, attributed to a diffusion-limited reaction between incoming NH3 and H3O+ located at or near the surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
(13 reference statements)
1
6
0
Order By: Relevance
“…Vibrational sum frequency generation studies have also provided evidence for the presence of unionized species on the surface of low-temperature liquid sulfuric acid. 25 One such species, a sulfuric acid/water 1:1 complex with the H 2 O molecule bridging the O and OH groups, gives predicted bond vibrations in good agreement with a species observed by Horn et al 26 in a number of ATR-IR experiments. The species was most easily observed in the ATR-IR experiments where the films had been deposited under extremely H 2 Odeficient conditions.…”
Section: Resultssupporting
confidence: 75%
“…Vibrational sum frequency generation studies have also provided evidence for the presence of unionized species on the surface of low-temperature liquid sulfuric acid. 25 One such species, a sulfuric acid/water 1:1 complex with the H 2 O molecule bridging the O and OH groups, gives predicted bond vibrations in good agreement with a species observed by Horn et al 26 in a number of ATR-IR experiments. The species was most easily observed in the ATR-IR experiments where the films had been deposited under extremely H 2 Odeficient conditions.…”
Section: Resultssupporting
confidence: 75%
“…Table 1 compares the peak positions of the major features in the three forms of MSSAH. There is very good agreement between the three forms, if systematic differences in the measurements methods are taken into account (also, the SAM surface MSSAH spectrum is very thin ((0.01 mm) and is obtained by subtraction of spectra of relatively thick films 24 ). Closer scrutiny reveals the presence of an additional poorly resolved features at ca.…”
Section: Mssah: Metastable Sulfuric Acid Hydratementioning
confidence: 80%
“…6b shows the spectrum of a thin surface layer of MSSAH recently identified as being on the surface on a thin film of SAM at ca. 200 K by Couling et al, 24 whilst Fig. 6c shows a condensed film consisting entirely of the same material at 190 K. Detailed assignment of the absorption bands of this material are presented elsewhere.…”
Section: Mssah: Metastable Sulfuric Acid Hydratementioning
confidence: 80%
“…1 Molecular hydrate complexes have been detected in sulfate aerosolsandtheirstabilityhasbeencorroboratedinexperiments. [15][16][17][18] In year 2004, the high polarity of H 2 SO 4 hydrates was predicted by Natsheh et al 19 Two years later, this finding has received an experimental conformation in the work of Leopold with coauthors, 13 who have reported dipole moment of 3.05 debyes for the most stable isomer of hydrogen-bonded (H 2 SO 4 )(H 2 O) at T ) 3 K.…”
Section: Introductionmentioning
confidence: 90%